Institutional Trust 2005 - Holmberg, Sören; Weibull, Lennart; MedieAkademin; TNS Gallup (University of Gothenburg, 2014)
Since 1997, MedieAkademin has carried out an annual survey titled The Institutional Trust. The survey has focused on major social institutions, such as the parliament, big business, the daily press, and TV/radio, as well as some specific companies such as Sveriges Television, TV4, IKEA, Skandia, and Volvo. The number of institutions included has varied somewhat over the years. Some of the institutions and companies have been measured every year while others have been investigated more irregularly.

The survey was carried out by TNS Gallup and involved 766 individuals who were interviewed by telephone between October 28 and November 14, 2005. The survey comprised 28 institutions/companies/brands and 10 leaders. The 2005 survey also included questions regarding opinions about the future.

Purpose:

To study the trust that Swedish people have in social institutions, political parties, media, brands/companies, and leaders.

MedieAkademins förtroendebarometer har genomförts årligen sedan 1997. Undersökningen har varje år dels avsett ett urval viktiga samhällsinstitutioner som exempelvis riksdagen, storföretagen, dagspressen och radio-TV, dels ett antal konkreta medier, bl.a Sveriges Television och TV4, och specifika företag, som t ex IKEA, Skandia och Volvo. Antalet bedömda institutioner har varierat något mellan enskilda år. Vissa av institutionerna/medierna/företagen har mätts varje år, andra har studerats mer oregelbundet.

Undersökningen 2005 omfattade 766 intervjupersoner och genomfördes 28/10 - 14/11 2005. För intervjuerna som görs per telefon har TNS Gallup (före 2004 NFO Infratest) i Göteborg svarat. I undersökningen ingår 28 institutioner/
företag/varumärken och 10 ledare. I 2005 års undersökning ingick även frågor om framtidsbedömningar.

Syfte:

Studera svenska folkets förtroende till samhällsinstitutioner, politiska partier, medier, varumärken/företag och ledare.
Förtroendebarometer 2005
Keywords: mass media; massmedia; trust; förtroende; political attitudes; politiska åsikter; trust in government; förtroende för regeringen; Media; Media; POLITICS; POLITIK; Social Sciences; Samhällsvetenskap